2019
DOI: 10.1590/2358-2936e2019018
|View full text |Cite
|
Sign up to set email alerts
|

External marking of terrestrial isopods (Isopoda, Oniscidea): efficiency of materials and influence on feeding behavior

Abstract: Many monitoring studies use marking techniques to obtain dispersal data on individuals. Marking procedures may influence the vital activities of the terrestrial isopods, such as feeding behavior. The objective of this study was to identify the efficiency of different materials for external marking of woodlice and the influence on their feeding performance. Cyanoacrylate glue + glitter and nail polish were used as separate marking materials on three species: Balloniscus glaber, Benthana picta and Armadillidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A wide range of marking techniques have been developed to evaluate the dispersal patterns of arthropods (Lavandero et al, 2004;di Lascio et al, 2016;Madeira and Pons, 2016;Jiao et al, 2019;Kenne et al, 2019;Tavares et al, 2019;Hagler and Machtley, 2020). El Sheikha (2019) reviews the advantages and disadvantages of several tracking techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of marking techniques have been developed to evaluate the dispersal patterns of arthropods (Lavandero et al, 2004;di Lascio et al, 2016;Madeira and Pons, 2016;Jiao et al, 2019;Kenne et al, 2019;Tavares et al, 2019;Hagler and Machtley, 2020). El Sheikha (2019) reviews the advantages and disadvantages of several tracking techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of two animals per arena only one animal was marked. It was reported previously that some external markers (e.g., nail polish) may affect diurnal activity and food consumption in some isopod species ( Drahokoupilová and Tuf 2012 ; Kenne et al 2019 ). However, our previous experiments have shown that the marking we used is less persistent and has no effect on animal activity.…”
Section: Methodsmentioning
confidence: 97%